A Stress Tensor-based Failure Criterion for Ordinary State-based Peridynamic Models - Daniele Dipasquale; Giulia Sarego; Prasert Prapamonthon; Soemsak Yooyen; Arman Shojaei (SHILAP Revista de lepidopterología, 2022)
Peridynamics is a recent nonlocal theory of continuum mechanics that is suitable to describe fracture problems in solid mechanics. In this paper, a new failure criterion based on the stress field is developed by adopting the damage correspondence model in the ordinary state-based peridynamic theory. The proposed stress tensor-based failure criterion is capable of predicting more accurately crack propagation in the mixed mode I-II fracture problems different from other failure criteria in peridynamics. The effectiveness of the proposed model is demonstrated by performing several examples of mixed-mode dynamic fracture in brittle materials.
Keywords: Numerical methods in engineering; Electromagnetic Simulation and Numerical Methods; Geotechnical Engineering and Underground Structures